Computational Methods for Understanding Riboswitches - Chen, Shi-Jie; Burke, Donald H. (Methods in enzymology, 2015)
This new volume of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers computational prediction RNA structure and dynamics, including such topics as computational modeling of RNA secondary and tertiary structures, riboswitch dynamics, and ion-RNA, ligand-RNA and DNA-RNA interactions. Continues the legacy of this premier serial with quality chapters authored by leaders in the field Covers computational methods and applications in RNA structure and dynamics.